Experimental Investigation of Condensation Phenomenon on Hydrophilic and Hydrophobic Titanium (Ti) Pillared Glass Surfaces - Haque, Mohammad Rejaul; Zhu, Chen; Qu, Chuang; Kinzel, Edward C.; Betz, Amy R. (My University, 2018)
Atmospheric condensation is very important for multiple practical applications such as heat transfer, aerospace, and water harvesting etc. Surfaces below the dew point temperature, heterogeneously nucleate water droplets on the surfaces. Gibbs free energy of heterogeneous nucleation barrier for a condensed droplet on a rough surface changes significantly with the change of humidity content. The influence of environmental factors and substrate characteristics (topology, surface chemistry, and substrate temperature) on atmospheric condensation is very important to elucidate the droplet shape and wetting state. Condensation from the humid air has been studied on Titanium (Ti) pillars and Teflon© coated Ti pillared glass surfaces in order to reveal the condensate harvesting and dropwise condensation applications.
Keywords: Condensation; Droplet; Relative humidity; Titanium pillars; Hydrophobic coating